Impact of Different BMIs on Fetomaternal Outcome as Compared to Control Group BMIs - Rehman, Mounazza; Ghaffar, Sadia; Nawaz, Qudsia; Gul, Uzma; Ashfaq, Tayyaba; Tabassum, Humaira (Biological and Clinical Sciences Research Journal, 2025)
Maternal body mass index (BMI) plays a pivotal role in determining fetomaternal outcomes. Deviations from the normal BMI range—whether underweight, overweight, or obese—are associated with adverse maternal and neonatal complications. As the global prevalence of abnormal BMI among women of reproductive age continues to rise, it is imperative to understand its impact on pregnancy outcomes to optimize prenatal care strategies. Objective: To evaluate and compare the fetomaternal outcomes across different maternal BMI categories—underweight, overweight, and obese—using women with normal BMI as the reference group, with a focus on maternal complications (e.g., pregnancy-induced hypertension (PIH), gestational diabetes mellitus (GDM), postpartum hemorrhage (PPH)) and neonatal indicators (e.g., birth weight, NICU admission). Methods: This cross-sectional observational study was conducted over six months at the Combined Military Hospital (CMH), Quetta from July 2023 to January 2024. A total of 200 third-trimester pregnant women with singleton pregnancies were selected via purposive sampling and stratified equally into four BMI categories—underweight, normal (control), overweight, and obese—based on World Health Organization (WHO) BMI criteria. Data on mode of delivery, maternal complications, and neonatal outcomes were collected using clinical records and semi-structured interviews. Statistical analysis involved the use of frequencies, percentages, and thematic content analysis to assess psychological factors. Results: Obese women exhibited the highest rates of cesarean delivery (48%), GDM (30%), PIH (24%), macrosomia (20%), and NICU admissions (28%). Overweight women also demonstrated increased risks across these categories, though to a slightly lesser degree. Underweight mothers had the highest incidence of low birth weight (36%), notable NICU admissions (12%), and assisted vaginal delivery (8%). Women with normal BMI consistently showed the most favorable outcomes across all variables. Thematic analysis revealed psychological distress related to body image, fear of surgical interventions, and reduced emotional support, especially among underweight and obese participants. Conclusion: Abnormal maternal BMI is significantly associated with poor fetomaternal outcomes. Underweight status predisposes to intrauterine growth restriction and neonatal morbidity, while obesity increases the risk of metabolic, hypertensive, and delivery-related complications. Optimal pregnancy outcomes are most consistently observed in women with normal BMI. These findings highlight the need for BMI-based prenatal risk stratification, targeted counseling, and integrated psychosocial support to improve maternal and neonatal health.